Cape Town crisis: An analysis on drought response measures, the motives behind them, and their implications for equitable water access - Koehler, Lara-Marie (Department of Environmental and Geographical Science, 2022)
Cape Town has recently undergone major policy and regulatory changes within its water management strategy in response to a three-year drought (2015-2018). Due to the vulnerability of humanity to climate change, its uncertainty, and the risks that it poses for securing a reliable source of water, it is important to fully understand the implications of Cape Town's responding water management changes, in understanding that similar events could occur again in the future. Situated within the field of political ecology, this research aims to determine how the evolution of water management in Cape Town in response to the drought will most likely impact the ideal of equitable water service provision throughout the city's post-crisis context. By utilizing a series of personally conducted semi-structured interviews and secondary official city documents, this research focuses on the tourism industry and the African Water Commons Collective (AWCC) as a lens to understand what motivated the CoCT's water-policy decision-making processes, how the economy and low-income communities were considered and treated in response to these decisions, how these have gone on to impact their respective experiences with water accessibility, and what this implies regarding their accessibility for the near future. The results reveal that a significant number of policy decisions were based on the emergence of a duality of crisis: (1) a drought that mandated reducing demand and augmenting supply and (2) a financial model in need of stabilizing in order for the department to be able to do so. The tourism industry and low-income communities indeed experienced the City's governance responses differently; their experiences each implying very different outlooks for their accessibility in the future. The tourism industry's position within the economy and local government has proven to make it better able to adapt and be resilient in the face of water shortages, painting a pretty picture for its future survival in the face of climate change. The strained relationship between low-income communities and local government, on the other hand, has proven to complicate the City's attempts to improve water and sanitation services in those areas. Without this communication, the City cannot expect to fully understand how the impacts of their decisions are influenced by the spatial and infrastructural contexts of low-income communities. For this reason, improvements in living conditions for those areas cannot be expected. Rather, it is important that the City recognizes the impacts its decisions have on accessibility for the poor, and why. Recognizing that similar events are increasingly likely in the future, at a global scale and with greater frequency, the ability of the Water and Sanitation Department (W&SD) to recognize, reflect and react to these conflicting objectives is crucial if equal water accessibility between citizen groupings is ever going to be met.